Safety, Tolerability, and Immunogenicity of the InvaplexAR-Detox Shigella Vaccine Co-Administered with the dmLT Adjuvant in Dutch and Zambian Adults: Study Protocol for a Multi-Center, Randomized, Double-Blind, Placebo-Controlled, Dose-Escalation Phase Ia/b Clinical Trial - Geert V. T. Roozen; Nsofwa Sukwa; Masuzyo Chirwa; Jessica A. White; Marcus Estrada; Nicole Maier; Kevin R. Turbyfill; Renee M. Laird; Akamol E. Suvarnapunya; Aicha Sayeh; Flavia D’Alessio; Candice Marion; et al. (Vaccines)
Background: Shigella infections remain endemic in places with poor sanitation and are a leading cause of diarrheal mortality globally, as well as a major contributor to gut enteropathy and stunting. There are currently no licensed vaccines for shigellosis but it has been estimated that an effective vaccine could avert 590,000 deaths over a 20-year period. A challenge to effective Shigella vaccine development has been the low immunogenicity and protective efficacy of candidate Shigella vaccines in infants and young children. Additionally, a new vaccine might be less immunogenic in a highly endemic setting compared to a low endemic setting (“vaccine hyporesponsiveness”). The use of a potent adjuvant enhancing both mucosal and systemic immunity might overcome these problems. InvaplexAR-Detox is an injectable Shigella vaccine that uses a novel combination of conserved invasion plasmid antigen proteins and a serotype-specific bacterial lipopolysaccharide attenuated for safe intramuscular administration. The adjuvant dmLT has been shown to enhance Shigella immune responses in mice, has safely been administered intramuscularly, and was shown to enhance immune responses in healthy volunteers when given in combination with other antigens in phase I trials. This article describes the protocol of a study that will be the first to assess the safety, tolerability, and immunogenicity of InvaplexAR-Detox co-administered with dmLT in healthy adults in low-endemic and high-endemic settings. Methods: In a multi-center, randomized, double-blind, and placebo-controlled dose-escalation phase Ia/b trial, the safety, tolerability, and immunogenicity of three intramuscular vaccinations administered 4 weeks apart with 2.5 µg or 10 µg of InvaplexAR-Detox vaccine, alone or in combination with 0.1 µg of the dmLT adjuvant, will first be assessed in a total of 50 healthy Dutch adults (phase Ia) and subsequently in 35 healthy Zambian adults (phase Ib) aged 18–50 years. The primary outcome is safety, and secondary outcomes are humoral and cellular immune responses to the adjuvanted or non-adjuvanted vaccine. Discussion: This trial is part of the ShigaPlexIM project that aims to advance the early clinical development of an injectable Shigella vaccine and to make the vaccine available for late-stage clinical development. This trial addresses the issue of hyporesponsiveness in an early stage of clinical development by testing the vaccine and adjuvant in an endemic setting (Zambia) after the first-in-human administration and the dose-escalation has proven safe and tolerable in a low-endemic setting (Netherlands). Besides strengthening the vaccine pipeline against a major diarrheal disease, another goal of the ShigaPlexIM project is to stimulate capacity building and strengthen global North-South relations in clinical research. Trial registration: EU CT number: 2023-506394-35-02, ClinicalTrials.gov identifier: NCT05961059.